Peningkatan Kemampuan Penalaran Matematika dan Sikap Siswa melalui Penerapan Pembelajaran Matematika dengan Pendekatan Open Ended pada Siswa Kelas VIII-2 SMPN 7 Padangsidimpuan - Yuni Rhamayanti; Nurdalilah Nurdalilah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
This research was conducted on junior high school students with the aim of improving mathematical reasoning abilities, student activity and student attitudes towards the application of open ended approach learning. This type of research is Classroom Action Research. The subject of this study is the eighth grade students of SMP Negeri 7 Padangsidimpuan 2017-2018 Academic Year, which are selected in class VIII-2 with a total of 24 students. The conclusions that can be drawn from this study are 1) increasing mathematical reasoning abilities through the application of mathematical learning with an open-ended approach to students of class VIII-2. The increase in students' mathematical reasoning abilities was obtained at 0.5 with the medium criteria, 2) increasing student learning activities through the application of mathematics learning with an open-ended approach to students of class VIII-2. The increase in student activity was obtained at 0.46 with moderate criteria, 3) increasing student attitudes towards mathematics through the application of mathematics learning with an open-ended approach to students of class VIII-2. The increase in student activity is 0.6 with moderate criteria.